Overview and prospects of plasma wakefield acceleration experiments at PITZ. (November 2019) - Lishilin, O; Chen, Y; Good, J; Gross, M; Isaev, I; Koschitzki, C; Krasilnikov, M; Loisch, G; Melkumyan, D; Niemczyk, R; Oppelt, A; Qian, H; et al.
Abstract: The Photo Injector Test Facility at DESY in Zeuthen (PITZ) carries out studies of beam-driven plasma wakefield acceleration (PWFA). The facility possesses a flexible photocathode laser beam shaping system and a variety of diagnostics including a high-resolution dipole spectrometer and an rf deflector which enables the observation of the longitudinal phase space of electron beams after their passage through a plasma. Two plasma sources are available: a gas discharge plasma cell and a photoionized lithium vapor plasma cell. Studies at PITZ include investigations of the self-modulation instability of long electron beams and the high transformer ratio, i.e., the ratio between the maximum accelerating field behind the drive beam and the decelerating field within the beam. This overview includes the experimental results and plans for future experiments.